A Longitudinal Study Evaluating Indications, Efficacy and Complications of Bronchial Artery Embolisation - Ganesh Nilpatrewar; Nagsen Ramraje; Vishwanath Pujari; Sanchit Mohan; Priti Meshram (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Embolisation is defined as the therapeutic introduction of Gelfoam or Poly-Vinyl Alcohol (PVA) particles into the circulation to occlude vessels. Selective embolisation of the bronchial arteries feeding the affected areas could be more effective than surgical intervention which is more hazardous leading to prolong Intensive Care Unit (ICU) stay, air leaks, stump infection. Aim: To study various indications, success rate, complications, and recurrence after Bronchial Artery Embolisation (BAE). Materials and Methods: The present longitudinal study was conducted in the Department of Pulmonary Medicine in collaboration with the Department of Interventional Radiology in Grant Medical College and JJ hospital, Mumbai, Maharashtra, India from December 2016 to December 2017. The study was done on 50 patients admitted in view of moderate to massive haemoptysis. Common indications requiring BAE, success rate with gelfoam or PVA particles, and common complications of the procedure were studied. Mean age of presentation with haemoptysis, co-morbidities associated with the disease were also studied. The patients were followed-up for six months. Repeat BAE was done in patients with PVA particles before referring for surgical intervention in cases with recurrent haemoptysis. Results: The mean age of patients requiring BAE was 37.98 years, with male predominance. Most common indication was pulmonary tuberculosis followed by post-tuberculosis sequelae. The overall success rate of the procedure was 88% at six months follow-up.BAE done with PVA (10/10) particle showed a better outcome as compared to gelfoam (34/40). The most common complication related to the procedure was puncture site pain. Three patients out of six with recurrent haemoptysis required repeat BAE within three months, out of which only one required surgery. Conclusion: The most common indication for BAE in this study was pulmonary tuberculosis. There were no major complications, even with repeat BAE. Hence, BAE should be the procedure of choice for moderate to massive haemoptysis despite of previous history of BAE, before considering for surgical intervention. BAE with PVA is associated with better success rate.